2014
DOI: 10.3171/2014.7.focus1496
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging in lumbar gunshot wounds: an absolute contraindication?

Abstract: Object Performance of MR imaging in patients with gunshot wounds at or near the lumbar spinal canal is controversial. The authors reviewed the literature on the use of MR imaging in gunshot wounds to the spine. They discuss the results from in vitro and clinical studies, analyze the physical properties of common projectiles, and evaluate the safety and indications for MR imaging when metallic fragments are located near the spinal canal. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, several studies have demonstrated that non-nickel and non-steel based bullets are safe to undergo MRI. 13 - 15 Venous lead levels are routinely drawn on GSW patients in order to obtain baseline values. If spinal instability is present, bracing is offered or surgical intervention consisting of instrumentation and fusion with removal of bullet fragment if encountered.…”
Section: Resultsmentioning
confidence: 99%
“…However, several studies have demonstrated that non-nickel and non-steel based bullets are safe to undergo MRI. 13 - 15 Venous lead levels are routinely drawn on GSW patients in order to obtain baseline values. If spinal instability is present, bracing is offered or surgical intervention consisting of instrumentation and fusion with removal of bullet fragment if encountered.…”
Section: Resultsmentioning
confidence: 99%
“…retained bullets from firearm injuries or fragments of missiles/bomb shells. The ferromagnetic metal objects can rotate and/or move in a magnetic field and thus possibly result in secondary damage [2,3,11].…”
Section: Discussionmentioning
confidence: 99%
“…MRI was deferred due to the presence of the metallic object. 2,3 The decision was made to conservatively manage her renal injury. She was planned for wound exploration and FB removal under general anesthesia.…”
Section: Introductionmentioning
confidence: 99%